1964
DOI: 10.1136/bmj.2.5402.141
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Liquor Amnii as a Method of Predicting Severity of Haemolytic Disease of Newborn

Abstract: The association of yellow amniotic fluid and hydrops foetalis has long been appreciated (Pickles, 1949) The tracings obtained show percentage absorption rather than optical density, so although the height of the peak is related to the quantity of pigment this relationship is logarithmic, not linear. Thus 10% absorption in the range zero to 10% absorption would give a peak in the tracing 10 times that produced by the same amount of pigment in the range 99-100% absorption. The effect of this is to minimize the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1965
1965
1976
1976

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Some workers have measured the difference in absorption between the peak at 450 nm and a tangent drawn between the lowest point at each end of the curve, referring to this as the 'estimated' bilirubin (Walker et al• 1964). Because the position of the tangent is arbitrary, other workers have proposed the use of ratios of absorbance at different wavelengths on the absorbance curve (White et al, 1958;Walker et al• 1964;Knox et al, 1965).…”
Section: Spectrophotometric Examination Of Amniotic Fluid For Bilirubinmentioning
confidence: 99%
See 1 more Smart Citation
“…Some workers have measured the difference in absorption between the peak at 450 nm and a tangent drawn between the lowest point at each end of the curve, referring to this as the 'estimated' bilirubin (Walker et al• 1964). Because the position of the tangent is arbitrary, other workers have proposed the use of ratios of absorbance at different wavelengths on the absorbance curve (White et al, 1958;Walker et al• 1964;Knox et al, 1965).…”
Section: Spectrophotometric Examination Of Amniotic Fluid For Bilirubinmentioning
confidence: 99%
“…Some workers have measured the difference in absorption between the peak at 450 nm and a tangent drawn between the lowest point at each end of the curve, referring to this as the 'estimated' bilirubin (Walker et al• 1964). Because the position of the tangent is arbitrary, other workers have proposed the use of ratios of absorbance at different wavelengths on the absorbance curve (White et al, 1958;Walker et al• 1964;Knox et al, 1965). Fleming and Woolf (1965) took readings at four wavelengths and corrected for the presence of oxyhaemoglobin and turbidity, and also for methaemoglobin after reduction by sodium hydrosulphite; Ovenstone and Connon (1968) used a spectrophotometric method to measure the slope of the absorbance curve at 490 nm and correlated this with the bilirubin concentration.…”
Section: Spectrophotometric Examination Of Amniotic Fluid For Bilirubinmentioning
confidence: 99%
“…This may either be the result of himolytic disease or of prematurity or both. Exchange transfusion has made it largely a preventable condition and further advances can be expected in the saving of feetal life along the lines indicated by Liley (1961), Walker et al (1964 and Robertson (1964), who have demonstrated how to predict the likely severity of hemolytic disease at about the thirtyfourth week of pregnancy before the damage has gone too far. Such information, in conjunction with the history, may help to modify obstetrical management and secure the delivery of a living child, whose outlook is good provided kernicterus can be prevented.…”
Section: Unfavourable Factors In Pregnancymentioning
confidence: 99%
“…In spite of the wide use that is now made of liquor analysis in assessing the severity of haemolytic disease (Bevis, 1956(Bevis, , 1967Walker, 1957;Mackay, 1961;Liley, 1963;Walker et al, 1964;Freda, 1965), opinions still differ on the merits of chemical (Wild, 1961;Watson, 1962;Robertson, 1964;Watson et al, 1965;Bower and Swale, 1966) compared with spectrophotometric (Liley, 1961;Alvey, 1964;Knox et al, 1965;Fleming and Woolf, 1965;Savage et al, 1966) methods of estimating bile pigment and on the formulation of diagnostic criteria likely to give the most accurate prognosis.…”
Section: Introductionmentioning
confidence: 99%